1991
DOI: 10.1002/ajpa.1330840203
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding in Finland

Abstract: We have compiled data on the frequency of first-cousin marriages in Finland using royal dispensation records for the time period 1810-1872 and national population statistics for the time period 1878-1920. For the earlier period, 0.315% of Finland's marriages were contracted between first cousins (2,331 of 739,387). During the second time period, 0.174% of Finland's marriages took place between first cousins (1,325 of 761,976). These figures, which yield average kinship coefficients of 0.00020 and 0.00011, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 33 publications
(18 reference statements)
1
24
0
Order By: Relevance
“…Inbreeding patterns in Guipú zcoa are rather similar to those recorded for other Basque territories in comparable periods of time (e.g., Alava; Calderón et al, 1993), and fit closely into the basic model of secular evolution of inbreeding recorded in other large Western European populations (Sutter and Tabah, 1948;Twiesselman et al, 1962;Moroni, 1967;Saugstad, 1977;McCullough and O'Rourke, 1986;Jorde and Pitkä nen, 1991). By contrast, in most Iberian populations, the decrease in inbreeding appears 3-4 decades later, coinciding with the takeoff of large-scale industrialization in Spain (PintoCisternas et al, 1979;Calderón, 1989;Gómez, 1989;Morales, 1992;Fuster et al, 1996).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Inbreeding patterns in Guipú zcoa are rather similar to those recorded for other Basque territories in comparable periods of time (e.g., Alava; Calderón et al, 1993), and fit closely into the basic model of secular evolution of inbreeding recorded in other large Western European populations (Sutter and Tabah, 1948;Twiesselman et al, 1962;Moroni, 1967;Saugstad, 1977;McCullough and O'Rourke, 1986;Jorde and Pitkä nen, 1991). By contrast, in most Iberian populations, the decrease in inbreeding appears 3-4 decades later, coinciding with the takeoff of large-scale industrialization in Spain (PintoCisternas et al, 1979;Calderón, 1989;Gómez, 1989;Morales, 1992;Fuster et al, 1996).…”
Section: Resultsmentioning
confidence: 73%
“…Consanguinity studies in small and large populations of the Basque area confirmed that the rates of close consanguineous matings (uncle-niece/auntnephew and first cousins) are unusually high in comparison to most Iberian and Western European population standards (Sutter and Tabah, 1948;Moroni, 1967;Pettener, 1985;Calderón, 1989;Jorde and Pitkä nen, 1991). In contrast to this pattern, mean inbreeding levels registered over a long time span in the Spanish Basque Country are not particularly high, except for some local populations (Abelson, 1978;Zudaire, 1981;Alfonso-Sá nchez et al, 1997;Peñ a et al, 2002).…”
mentioning
confidence: 80%
“…Within northern Scandinavia, studies based on royal dispensation records and national population statistics show a very low level of first cousin marriage in Finland during the 19th century, although, as in northern Sweden, parishes with a substantial Saami population were an exception (Jorde & Pitkänen, 1991). Avoidance of first cousin marriage appears to have resulted both from the requirement for royal dispensation payments, which continued in Finland until 1872, and a cultural prohibition in parts of eastern Finland against paternal parallel cousin marriages (Jorde & Pitkänen, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of first cousin marriage appears to have resulted both from the requirement for royal dispensation payments, which continued in Finland until 1872, and a cultural prohibition in parts of eastern Finland against paternal parallel cousin marriages (Jorde & Pitkänen, 1991). The latter prohibition may have stemmed from the restrictions on cousin marriage applied by the Christian Orthodox Church, which would have been quite influential in regions of the country bordering on Russia (Ignatius, 1994(Ignatius, -1995.…”
Section: Discussionmentioning
confidence: 99%
“…Inbreeding is by no means limited to small isolates; low levels of inbreeding have also been observed in large "open" populations (Cavalli-Sforza and Bodmer, 1971;McCullough and O'Rourke, 1986;Czeizel et al, 1976;Jorde and Pitkanen, 1991;Dahlberg, 1938;Sutter and Goux, 1962;Woolf et al, 1956). Scientific interest, however, has been focused on smaller, more isolated populations wherein inbreeding has been found to be associated with a pronounced incidence of recessive disorders (Bailit et al, 1966;Hussels, 1969;Ghosh and Majumder, 1979;Pollock et al, 1972;O'Brien et al, 1988;Khoury et al, 1987).…”
mentioning
confidence: 90%